(untitled) - Smith, G. Elliot (London, 1933)
The aim of this book is to examine the writíng of those writers who have been mainly responsible for the evidence thay themselves have provided.
Keywords: Civilization,Anthropology,Văn minh,Nhân học; History,Lịch sử